Discrimination based on gender and disability against sexual violence victims: Case-law analysis - Charaja Coata, María Luisa (2022)
This paper identifies the vulnerability factors of gender and disability discrimination against victims of sexual violence from an intersectional discrimination approach. Importance thereof is practical from the role of the administrator of justice in the protection, investigation, and punishment, who, in addition, must identify those factors of vulnerability present in a sexual violence case. For this purpose, a conventional case-law case is analyzed: R.P.B. vs. the Philippines (Communication No. 34/2011). This analysis starts from the revision of the normative and national and international case-law framework. It concludes that administrators of justice must put aside gender stereotypes in order to identify the multiple vulnerability factors that arise in a sexual violence case, and thus guarantee the right to access to justice.